Fate of phosphorus and potassium in gasification of wheat bran and sunflower seed shells - Schmid, Daniel; Olsson, Emil Lidman; Vainio, Emil; Wu, Hao; Karlström, Oskar; Hupa, Leena (ELSEVIER SCI LTD, 2025)
Thermal conversion of agricultural biomass residues poses a great opportunity to valorize waste materials by recovering energy and valuable elements such as phosphorus. Utilizing biomass residues in thermal conversion is, on the other hand, often coupled with operational challenges due to particle emissions, deposit formation, corrosion and slagging caused by the ash-forming elements in the biomass. A detailed understanding of the ash chemistry is required when utilizing those fuels to reduce these operational problems and recover valuable elements from the ash. However, predictions for ash transformation are often always reliable when using existing thermodynamic data and ash transformation mechanisms. The present work investigated the release of phosphorus and potassium during gasification of two seed-originated agricultural biomass residues, wheat bran and sunflower seed shells, at 900-1100 degrees C in 3 % O2 or 10 % CO2 (rest N2). The residues were characterized by scanning electron microscopy (SEM), X-ray diffraction (XRD) and inductively coupled plasma optical emission spectroscopy (ICP-OES). During the gasification of wheat bran, phosphorus and potassium were partly released to the gas phase, while only potassium was released to the gas phase during the gasification of sunflower seed shells. The residues from the gasification of wheat bran contained mainly K-Mg-phosphates, while phosphorus was identified as hydroxyapatite in the sunflower seed shell residues. The experimental observations for wheat bran are in contradiction with predictions from thermodynamic equilibrium calculations, which suggest that all phosphorus remains in the residues. The discrepancy between the experimental and calculated results may be due to carbothermic reduction of phosphates, i.e. reactions between phosphates and carbon. As the occurrence of carbothermic reduction reactions is connected to the kinetics of the carbon consumption, it is suggested that thermodynamic data alone is not sufficient to correctly predict the ash chemistry in thermal conversion processes of phosphorus rich biomass fuels.